Diffusion and mobility of native point defects in narrow-gap Hg₁-xCdxTe crystals - Elizarov, A.I.; Kurbanov, K.R.; Bogoboyashchyy, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Results of investigations of mercury vacancy diffusion in the narrow-gap Hg₁-xCdxTe crystals are presented. A new theory for mercury diffusion in a gradient of native defect concentration is proposed. The theory takes into account the effect of charged defect drift in the internal electric field arising in the crystal at such process. Using this theory, the mercury vacancy diffusion coefficient in the Hg₁-xCdxTe (x ~ 0.2) crystals at 384-690 K has been found: DV = cm²/s. The result is found by fitting the experimental diffusion distribution of the vacancies obtained by a reliable optical method of local free carrier concentration measurements, on the one hand, and data of vacancy coagulation rate measurements, on the other hand. The mercury vacancy diffusion runs rather slowly at T < 690 K.